A Survey on Current Practices of Umbilical Cord Clamping in Malaysia - Pong, Kwai Meng; Puasa, Norezliani; Mahdy, Zaleha Abdullah (Frontiers in Medicine, 2022)
Background: Delayed cord clamping (DCC) has been demonstrated to have significant benefits in reducing the incidence of intraventricular hemorrhage, blood transfusion and neonatal mortality in preterm neonates and improving hemodynamic and long-term neurodevelopment among term infants. There is no clear guideline on umbilical cord clamping (UCC) practices in Malaysia. Objective The aim of this survey was to assess the knowledge and practice of DCC among obstetric doctors and midwives in Malaysia, and pediatric colleagues who witness the delivery. Method This is a cross-sectional survey conducted in childbirth facilities in Malaysia from October 2020 to January 2021. A convenient snowball sampling was adopted. A validated questionnaire was disseminated to practicing obstetric and pediatric doctors and midwives electronically via email and WhatsApp using Google Form. The data were analyzed using descriptive and analytical statistics. Results A total of 327 respondents completed the questionnaires, comprising 206 obstetric doctors, 72 pediatric doctors and 49 midwives. The majority of respondents were specialists or higher in rank (53.2%). Only 29% reported the existence of guidelines on UCC in their place of work. Midwives (P=0.003) and staff of lower ranks and level of education (P<0.001) appeared to be more aware of the existence of a UCC guideline. Most respondents had positive knowledge of DCC for both term and preterm neonates. A large proportion (82%) of respondents agreed that DCC helped increase neonatal iron stores, and was good for both preterm (70.7%) and term (76.2%) neonates not requiring positive pressure ventilation. Doctors, specialists, those who are 40 years old and above, and those who have been in service for at least 10 years were found to have better knowledge regarding DCC. (P<0.05) Conclusion The awareness and practice of obstetric, pediatric and midwifery staff of guidelines on UCC were less than satisfactory. Even though most respondents have good knowledge and positive perception regarding benefits of DCC, these were not translated into their routine practice. Hence, a national guideline emphasizing the benefits of DCC should be made available in all childbirth facilities.